Jagoan Bisnis: Optimisme Mencetak Wirausaha Muda Dalam Rangka Pemulihan Ekonomi di Banyuwangi - Elok Rosyidah; Sahru Romadloni; Sinta Tri Lestari (Universitas Muhammadiyah Jember, 2025)
The economy of the Banyuwangi community due to unemployment, starting from 2020, reached 5.34 percent and even in 2021 touched 5.42 percent. This is an optimistic step by the Banyuwangi Government in forming or creating young entrepreneurs. So that the economy and unemployment rate in Banyuwangi can develop towards a better direction. One of the supporting factors, through the Banyuwangi Government's launch program, namely Jagoan Banyuwangi with one of its incubation programs Jagoan Bisnis, to print hundreds of local young people to become entrepreneurs and encourage economic recovery in Banyuwangi. This study was conducted for 4 months from June 2023 to September 2023, with an allocation of 2 months for data collection and 2 months after for data analysis. The results of the statistical test of the difference in means after treatment in the experimental group and the control group with the help of the SPSS program obtained the mean value of the experimental group test results of 74.71 and the control group 66.67. Due to the T test value with a significance level smaller than 0.025 (0.011 < 0.025), it can be concluded that there is a difference in means between the experimental group and the control group. This means that the implementation of Jagoan Bisnis has a significant and positive effect on the learning process.